Mat Play Centers as an Innovation in Early Childhood Education - Nurani, Yuliani; Hartati, Sofia (Universitas Negeri Semarang, 2017)
Mat Play Center (‘Gelaran’ Play Center) is another innovation and advance in early childhood learning. In line with the purpose of research, first, pre-development the media of Mat Play Center (Gelaran Play Center) would collect data starting with theoretical framework and information based on the class or the field situation; second, the progress of media development in Mat play centers based on multiple intelligence is conceptual model development, design and products; while the third phase is the stage of the application form of testing the models which running in the field. The results showed in the form of design and media product of Mat play centers based on multiple intelligence that was developed based on the classification of creative play, specifically: the creation of objects; serialize games; creative questions games; creative movement games; as well as creative drama games.